126 Pre- and post-partum supplementation of molasses/urea, with or without methionine fortification, to enhance growth and physiology of Bos indicus-influenced primiparous cows and their offspring. (28th November 2020) - Palmer, Elizabeth; Vedovatto, Marcelo; Ranches, Juliana; Gouvea, Vinicius; Oliveira, Rhaiza; Arthington, John; Vendramini, Joao; Moriel, Philipe
Abstract: A 2-yr study evaluated the effects of molasses/urea supplementation during pre- and early postpartum, with or without methionine fortification, on growth and physiology of primiparous cows and their offspring. On d 0 of each yr, 36 cows were stratified by BW and BCS (396 ± 54 kg; 5.67 ± 0.66) and randomly assigned to 1 of 12 bahiagrass pastures (3 cows and 1.2 ha/pasture). Treatments were randomly assigned to pastures (4 pastures/treatment) and consisted of no supplementation (NOSUP), 1 kg/d of molasses/urea (MOL; DM basis), or 1 kg/d of MOL + 18 g/d of methionine hydroxy analog (MOLMET; Alimet, Novus, St. Charles, MO). Supplementation began 56 d before parturition (d 0) and ended when all cows within each pasture had calved (d 74). Calves were early weaned on d 147. On d 154, 24 calves (8 calves/treatment) were transferred to individual drylot pens, and offered ad libitum stargrass hay plus soybean hulls-based concentrate DM (75% TDN; 22% CP) at 3% of BW for 47 d. On d 160, calves were vaccinated against bovine viral diarrhea virus-1 (BVDV-1) and parainfluenza-3 (PI-3). Data were analyzed using the MIXED procedures of SAS. Cow BCS at calving was greater (P ≤ 0.05) for MOL and MOLMET vs. NOSUP but the overall percentage of pregnant cows did not differ among treatments (P = 0.82). Calf ADG from birth to drylot exit did not differ (P = 0.83) between MOL and MOLMET but was least (P ≤ 0.04) for NOSUPP calves. Seroconversion to BVDV-1 and PI-3 viruses were greater (P ≤ 0.05) for MOL and MOLMET vs. NOSUP calves. Hence, cow supplementation of molasses/urea during pre- and early postpartum improved cow prepartum BCS, and calf growth and humoral immunity. Methionine fortification of supplements did not impact cow and calf performance.